The dignity of resistance : women residents' activism in Chicago public housing - Feldman, Roberta M. (Cambridge series in environment and behavior., 2004)
This comprehensive case study chronicles the four decade history of Chicago's Wentworth Gardens public housing residents' grassroots activism. It explores why and how the African-American women residents creatively and effectively engaged in organizing efforts to resist increasing government disinvestment in public housing and the threat of demolition.